Psychosocial Correlates of Frailty Among HIV-Infected and HIV-Uninfected Adults. Issue 3 (3rd July 2019) - Rubtsova, Anna A.; Marquine, María J.; Depp, Colin; Holstad, Marcia; Ellis, Ronald J.; Letendre, Scott; Jeste, Dilip V.; Moore, David J.
Abstract: Frailty is a geriatric condition characterized by increased vulnerability to physical impairments and limitations that may lead to disabilities and mortality. Although studies in the general population suggest that psychosocial factors affect frailty, less is known about whether similar associations exist among people living with HIV (PLWH). The purpose of this study was to examine psychosocial correlates of frailty among PLWH and HIV-uninfected adults. Our sample included 127 adults (51% PLWH) participating in the Multi-Dimensional Successful Aging among HIV-Infected Adults study at the University of California San Diego (average age 51 years, 80% male, 53% White). Frailty was assessed via the Fried Frailty Index. Psychosocial variables significant in bivariate models were included in principal component analysis to generate factor variables summarizing psychosocial correlates. Multivariate logistic regression models were fit to examine the independent effects of factor variables and their interaction terms with HIV status. In bivariate models, frailty was associated with multiple psychosocial variables, for example, grit, optimism, personal mastery, social support, emotional support. Factor analysis revealed that psychosocial variables loaded on two factors—Positive Resources/Outlook and Support by Others. The multivariate model showed significant main effects of Support by Others and HIV status, and interactive effects HIV X Positive Resources/Outlook, such that Positive Resources/Outlook was negatively associated with frailty for PLWH but not for HIV-uninfected individuals. These analyses indicate that psychosocial factors may be associated with frailty among PLWH. Positive resources and outlook may play a role in frailty prevention. Future longitudinal studies are needed to establish causal links.